Analisis Determinan Penanaman Modal Asing Langsung Di 20 kota di Indonesia Periode 2004– 2008 - Neni Sri Wulandari (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2018)
Indonesiais adeveloping country where investmentbecomesa very important factortospureconomicgrowthandmacroeconomic performance. However, investment inIndonesiahas notbecome attractivefor investors toinvestinIndonesia. This study aimstoanalyzethe factorsthat affectforeign direct investment(FDI) in 20cities inIndonesiaduring the period2004 to 2008. Regressionmodelisusedas an analytical toolis a model offixedeffectpaneldataregressionmodel (FEM). Variables usedin this study arerealGDP, the CorruptionPerceptionIndex(CPI), CityMinimumWage(CMW), Inflation, Infrastructure, CrimeRate. While thecityis used asthe unitof analysisas many as20 citiesover the period2004, 2006, and 2008. Based on the resultsobtainedrealGDP and CPI, have positiveand significant impact onFDI. Meanwhile, City Minimum Wage, Inflation, and thecrime ratehave significantnegativeeffectonFDI. As for theinfrastructurevariableit hasnot significanteffectonFDI. Key Indicators : FDI, Real GDP, CPI City Minimum Wage, Crime Rate